Strategi Literasi Digital Berbasis Nilai Akhlakul Karimah untuk Membentengi Generasi Z di Era Artificial Intelligence - Zidni Darissalam; Imam Safe'i; Abdul Halim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of Artificial Intelligence (AI) has significantly transformed the lives of Generation Z, particularly in communication patterns, identity formation, and digital media usage. However, these advancements have also contributed to various moral issues such as the spread of hoaxes, cyberbullying, hedonistic culture, and the weakening of ethics and spirituality among young people. This study aims to analyze digital literacy strategies based on the values of akhlakul karimah as an effort to protect Generation Z from the negative impacts of AI. The research employed a qualitative approach using the library research method. Data were collected through the analysis of scientific literature, books, journal articles, and other relevant sources related to Islamic education, digital literacy, Generation Z, and AI development. Data analysis was conducted using descriptive-analytical content analysis. The findings indicate that the internalization of akhlakul karimah values through digital literacy can be implemented through three main strategies: reconstructing Islamic education learning based on digital contexts, strengthening family roles through Islamic digital parenting, and developing positive digital content ecosystems. Values such as shidq, amanah, ukhuwah, and hikmah serve as essential foundations in shaping the digital character of Generation Z. This study emphasizes that integrating Islamic education with digital literacy is a strategic approach to developing a generation that is technologically competent while remaining morally and spiritually grounded in the AI era.